The new African Americans - Ashabranner, Brent K., 1921-; Ashabranner, Jennifer (North Haven, Conn. : Linnet Books, 1999)
Looks at Africans who have immigrated to the United States since the 1890s, examining who they are, why they came, how American laws work for and against them, and how they have fared.
Includes bibliographical references (p. 103-104) and index.
The Balch Institute Library and Archives
Keywords: Immigrants -- United States -- Juvenile literature; Africans -- United States; Immigrants; Africans -- United States -- Juvenile literature; United States -- Emigration and immigration -- History -- Juvenile literature; Africa -- Emigration and immigration; United States -- Emigration and immigration; Africa -- Emigration and immigration -- History -- Juvenile literature